Native Potatoes: From Forgotten Crop to Culinary Boom and Market Innovation - Devaux, A.; Hareau, Guy; Ordinola, M.; Andrade-Piedra, J.L.; Thiele, Graham (Agricultural and Applied Economics Association, 2021)
Once neglected by urban consumers, Andean native potatoes are now essential ingredients for some of the most sophisticated gastronomy of the world. From colored chips to delicacy vegetables and even liquors, new products are making their way into high-income market niches. At the same time, native potatoes continue to fulfill their basic role of providing food security for many rural households in the Andes, who were responsible for domesticating them. Today, these families continue to plant native potatoes in diverse varietal mixtures which could contribute to longer term adaptation to climate change. The International Potato Center (CIP) found an opportunity for repositioning potato as an added-value cash crop. CIP has accomplished this by expanding its use for processing and by encouraging sales of improved and native potatoes to satisfy preferences of consumers in emerging markets in small and large cities and export markets. In this article, we examine how potatoes—particularly native potatoes—can improve livelihoods among poor farmers in Peru, highlighting the role of biodiversity as a resource to link small producers with markets. We offer examples with an approach to foster pro-poor innovation in value chains, the Participatory Market Chain Approach (PMCA), which was originally developed to increase the competitiveness of small-scale potato producers by taking advantage of the diversity of native potatoes. These native potato varieties have been successfully marketed to consumers who link them with Peru’s cultural heritage and who wish to support traditional, small-scale farming with relatively low external inputs